Legal Institution of Adoption in Peru - Mejía Salas, Pedro Andrés Francisco (2015)
Adoption is a means to overcome the situation of helplessness of those children and adolescents, mainly as a result of natural phenomena or inner and outer conflagration generated orphan status devoid of paternal or maternal protection, as the case.